Alterations in Cholesterol Metabolism and Genetics as Key Players in Mild Cognitive Impairment (P15-023-19) - An, Yu (Curr Dev Nutr, 2019)
OBJECTIVES: Alteration of circulating cholesterol precursors and oxidation products, in the form of sterols and oxysterols, has been demonstrated in Alzheimer's disease (AD) progression and its preclinical stage, mild cognitive impairment (MCI). However, limited species of metabolites were detected with the methods that do not discriminate between free and esterified forms, the former of which is the biologically active form. This study was aimed to identify MCI-associated differences in cholesterol metabolism by detecting a broad range of cholesterol synthetic and metabolic profiles in free form and their interplay with genetic variations for cholesterol homeostasis. METHODS: We conducted a pilot case–control study in a well-characterized Chinese cohort entitled the Effects and Mechanism Investigation of Cholesterol and Oxysterol on Alzheimer's disease (EMCOA) study including 100 MCI cases, each matched to one control participants. A broad range of non-esterified circulating cholesterol synthetic precursors and oxidation products were measured by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). A total of 21 tag single nucleotide polymorphisms (TagSNPs) in ApoE, CYP27A1, CYP46A1, CH25H, CYP7A1 and CYP7B1 was selected and genotyped by the Sequenom MassArray system. RESULTS: A total of 31 non-esterified cholesterol metabolites including 9 precursors and 22 oxysterols were detected in serum. We found significantly higher levels of 1 precursor and 11 oxysterols whereas lower levels of 3 oxysterols in MCI cases as compared to the controls. The random forest analysis showed that a biomarker panel of 20 lipids classified MCI patients with area under the curve (AUC) of 0.794 (95% CI = 0.694–0.868). With respect to SNPs, a QTL analysis identified 8 SNPs that were significantly associated with levels of 5 precursors and 14 oxysterols. CONCLUSIONS: The findings indicate that cholesterol metabolism is disrupted in MCI patients and correlating their profiles with genotype may provide productive insight into cognitive dysfunction and lead to new treatment strategies. FUNDING SOURCES: This work was supported by the State Key Program of the National Natural Science Foundation of China (Grant No. 81330065). SUPPORTING TABLES, IMAGES AND/OR GRAPHS: